Anti-diabetic effect of loganin by inhibiting FOXO1 nuclear translocation via PI3K/Akt signaling pathway in INS-1 cell - Fang-Fang Mo (Iranian Journal of Basic Medical Sciences, 2019)
Objective(s): JiangTangXiaoKe (JTXK) granule, a Chinese traditional herbal formula, has been clinically used and demonstrated to be beneficial in controlling high glucose and to relieve the symptoms of  Type 2 diabetes mellitus patients for decades. In this study, we explored how loganin, one of the components in JTXK granule, mediated the anti-diabetic effect.Materials and Methods: We generate a cell model with the dysfunction of insulin secretion by over-expression FOXO1 in INS-1 cells. MTT method was used to detect cytotoxicity after treated with Loganin. ELISA analysis was used to examine insulin secretion. The expression levels of FOXO1 and Akt were evaluated by Western blot.Results: Treatment with Loganin did not change the expression level of FOXO1 in INS-1 cells, but increased phosphorylation of FOXO1 and inhibited the nuclear translocation and accumulation of FOXO1, which improved the insulin secretion of the cells. Mechanistically, we found PI3K/Akt signaling pathway involved in these effects, which were blocked by an Akt inhibitor, LY294002.Conclusion: Loganin mediated the subcellular distribution of FOXO1 via PI3K/Akt signaling pathway, which protected the function of insulin secretion in islet INS-1 cells.